2021
DOI: 10.1016/j.celrep.2021.108978
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics identifies gene expression networks driving differentiation and tumorigenesis in the human fallopian tube

Abstract: The human fallopian tube harbors the cell of origin for the majority of high-grade serous ''ovarian'' cancers (HGSCs), but its cellular composition, particularly the epithelial component, is poorly characterized. We perform single-cell transcriptomic profiling of around 53,000 individual cells from 12 primary fallopian specimens to map their major cell types. We identify 10 epithelial subpopulations with diverse transcriptional programs. Based on transcriptional signatures, we reconstruct a trajectory whereby … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 71 publications
6
71
1
Order By: Relevance
“…Lawrenson et al [ 97 ] recently investigated the transcriptomic profiles of ovarian surface epithelial cells and fallopian tube secretory epithelial cells and compared them to bulk RNA profiles of HGSTOC, confirming that most of the HGSTOC derived from the latter. Furthermore, Dinh et al [ 98 ] performed single-cell RNA sequencing on fallopian tube specimens of 8 healthy patients and found a population of early secretory cells of which transcriptomic profile was maintained in advanced HGSTOC tumours. Interestingly, a lot of the proposed genes describing this early secretory cell subcluster (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Lawrenson et al [ 97 ] recently investigated the transcriptomic profiles of ovarian surface epithelial cells and fallopian tube secretory epithelial cells and compared them to bulk RNA profiles of HGSTOC, confirming that most of the HGSTOC derived from the latter. Furthermore, Dinh et al [ 98 ] performed single-cell RNA sequencing on fallopian tube specimens of 8 healthy patients and found a population of early secretory cells of which transcriptomic profile was maintained in advanced HGSTOC tumours. Interestingly, a lot of the proposed genes describing this early secretory cell subcluster (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…35,76 The emergence of singlecell transcriptomic data in cell types relevant to endometriosis and EOC offer further opportunities to explore potential celltype-specific effects on candidate genes. [42][43][44]77 ENOC and CCOC are believed to arise from ectopic (endometriosis-derived) or eutopic endometrial epithelium, while HGSOC is presumed to originate from fallopian tube secretory epithelial cells. 78 Despite the distinct cells of origin, we have previously shown that inherited genetic susceptibility to ENOC/CCOC and HGSOC is, to some extent, shared.…”
Section: Discussionmentioning
confidence: 99%
“…35,76 The emergence of single-cell transcriptomic data in cell types relevant to endometriosis and EOC offer further opportunities to explore potential cell-type-specific effects on candidate genes. 42 , 43 , 44 , 77 …”
Section: Discussionmentioning
confidence: 99%
“…Gene expression normalization and cell clustering was done using the SCTransform pipeline (21) with percent mitochondrial reads regressed out and person specific batch effects corrected using Harmony (22). Identification of cell clusters was done using known marker genes (Additional File 2: Table S1) (23)(24)(25)(26)(27)(28)(29)(30) with differential gene expression calculated using a Wilcoxon rank sum test. Enrichment of cell clusters of specific phenotypes was done using MASC (mixed-effects modeling of associations of single cells) (https://github.com/immunogenomics/masc), which essentially uses a percentage of cells per cluster while also taking into account technical covariates; 10x library batch, preparation (whole ME or ME-tissue), nUMI per cell, percent mitochondrial reads and phase are accounted for.…”
Section: (Mean ± Standard Deviation [Sd]mentioning
confidence: 99%